Tourism Advertisement Management and Effective Tools in Tourism Industry - Salehi, Hassan; Farahbakhsh, Morteza (International Journal of Geography and Geology, 2014)
The definition of tourism “is the travel for recreational, leisure, family or business purposes, usually of a limited duration. Tourism is commonly associated with trans-national travel, but may also refer to travel to another location within the same country”. Tourism as an industry, in today’s modern language is a means of global communication between nations and travelers of all countries, introducing them to the various cultures and societies abroad, as well there history, ancient, historical sites, and languages. Hence, advertising overall has become a tool of necessity in this ever-growing global industry. Given that, tourism is a part of the infrastructure of any country’s economy the growth and development of tourism is of great importance. Advertising plays a vital and is a crucial tool in developing the countries tourism by attractively presenting the nations points-of-interests, historical and cultural. Advertising has a central role in expanding this industry, generating economic growth in this area, as well as creating direct and indirect employment, but most importantly a creative innovating competition in the national and international travel industry. Importantly, to achieve a successful tourist industry, the Travel Agencies and governmental offices of the Ministry’s of Tourism and Business must work hand-in-hand to attain these goals. This article shows the impact of the various media and advertising methods used in tourism, which assisted in identifying the correct tool for expanding the country’s industry of tourism. The results of this study illustrated that the appropriate tools for promotional strategies to attract domestic and foreign traveler’s, found to be the most effective were, handbook, internet advertising, TV, brochures, newspapers.